Mental construal and perceived job control as antecedents of emotional labor and well-being - Daniels, M. A. (Institutional Knowledge at Singapore Management University, 2014)
Research on surface acting (i.e., faking or suppressing emotions to meet display rules) and deep acting (i.e., attempting to experience emotions to meet display rules) indicates that surface acting typically has substantial negative effects on employee well-being, whereas deep acting has displayed weaker relationships with employee well-being (Hülsheger & Schewe, 2011). We conducted two studies that sought to identify antecedents of emotional labor and employee well-being. Using construal level theory, we theorized that “high-level agents” (i.e., individuals with a higher mental construal who tend to identify their actions in terms that are more abstract) are less likely to surface act and more likely to deep act as compared to “low-level agents” (i.e., individuals with a lower mental construal who tend to identify their actions in terms that are more concrete), thus leading to more beneficial well-being outcomes. Additionally, we proposed a two-stage moderating role of perceived job control such that control moderates both the relation from mental construal to surface acting and the relation from surface acting to well-being. Results from two studies conducted in Singapore and the U.S. on employees across industries indicate that mental construal indirectly improves well-being through the decreased use of surface acting. Additionally, the negative effect of mental construal on surface acting was stronger when perceived job control was high. The results were relatively more mixed regarding the moderating role of job control on well-being and the relation between mental construal and deep acting. This study contributes to our limited understanding of the conditions under which employees are motivated to surface or deep act as well as the conditions under which surface acting affects well-being.